2008
DOI: 10.2174/1875039700801010040
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomic Analysis of Formalin Fixed Paraffin Embedded Oral HPV Lesions from HIV Patients

Abstract: Human immunodeficiency virus (HIV) infection is associated with dysplastic changes in oral human papilloma virus (HPV) lesions, suggesting changes in keratinocytes. In the present study, we seek to identify proteomic changes in oral HPV lesions between HIV(+) and HIV(-) patients. While fresh tissues represent the most desirable samples for proteomic investigations, they are often difficult to obtain in large numbers under clinical settings. We therefore have developed a new method to identify protein changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 24 publications
0
39
0
Order By: Relevance
“…Peptides derived from viable samples were labeled with iTRAQ tags 114 and 115, whereas peptides derived from apoptotic samples were labeled with iTRAQ tags 116 and 117. The labeled samples were then mixed together and fractionated via strong cation exchange and reverse phase chromatography according to a procedure described previously (33). The HPLC eluate was mixed with a matrix solution (7 mg/ml ␣-cyano-4-hydroxycinnamic acid in 60% acetonitrile, 5 mM ammonium monobasic phosphate, and internal mass calibrants (50 fmol/l each [Glu 1 ]fibrinopeptide B and ACTH (18 -39)) through a 30-nl mixing tee and directly spotted onto the MALDI plates.…”
Section: Methodsmentioning
confidence: 99%
“…Peptides derived from viable samples were labeled with iTRAQ tags 114 and 115, whereas peptides derived from apoptotic samples were labeled with iTRAQ tags 116 and 117. The labeled samples were then mixed together and fractionated via strong cation exchange and reverse phase chromatography according to a procedure described previously (33). The HPLC eluate was mixed with a matrix solution (7 mg/ml ␣-cyano-4-hydroxycinnamic acid in 60% acetonitrile, 5 mM ammonium monobasic phosphate, and internal mass calibrants (50 fmol/l each [Glu 1 ]fibrinopeptide B and ACTH (18 -39)) through a 30-nl mixing tee and directly spotted onto the MALDI plates.…”
Section: Methodsmentioning
confidence: 99%
“…Only one report utilized iTRAQ technology in conjunction with a commercial extraction kit in a quantitative proteomic study of FFPE tissues (Jain et al 2008). In 2005, a report described the successful application of shotgun proteome analysis combined with trypsin-mediated 18 O labeling to FFPE tissues of cancerous prostate lesions and benign prostate hyperplasia, opening the door to comparative proteomic analyses of FFPE tissues (Hood et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…To date, only one report has described the application of iTRAQ technology in a quantitative proteomic study of FFPE tissues; this report adopted the liquid tissue sample preparation method. The study successfully compared the expression of 114 proteins identified by at least two peptides from oral human papillomavirus lesions between human immunodeficiency virus (HIV)-positive and HIV-negative patients, and the expression level of KRT17 was corroborated by IHC (Jain et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The Liquid Tissue method has also been used for proteomics studies of a variety of FFPE tissue samples, including pancreatic tumors, 28 squamous cell carcinoma, 4 and oral human papillomavirus lesions. 27 …”
Section: Liquid Tissue ™ Methods For Protein From Ffpe Tissuementioning
confidence: 99%